2022
DOI: 10.1002/ajh.26699
|View full text |Cite
|
Sign up to set email alerts
|

Converting adults with sickle cell disease from full agonist opioids to buprenorphine: A reliable method with safety and early evidence of reduced acute care utilization

Abstract: Buprenorphine, a novel opioid with complex pharmacology, is effective for treating pain and is qualitatively safer than high-dose full agonist opioid therapy; but transitioning to buprenorphine can be technically complex and carries some risk of precipitated withdrawal. We report our clinic's experience converting 36 patients with sickle cell disease (SCD) from full agonist opioids to buprenorphine using a method developed in the past 10 years. Thirty of these patients were induced using a standard outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…While previous studies have focused on classical manifestations, there is a lack of literature addressing atypical presentations and their unique features, including the absence of acute pain and the development of complications such as thrombotic events and acute chest syndrome [ 9 , 10 ]. Understanding the heterogeneous nature of sickle cell disease is crucial, as it presents a wide range of clinical manifestations [ 11 , 12 ]. Diagnostic challenges are encountered in identifying atypical sickle cell crises, as evidenced by the delayed diagnosis in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have focused on classical manifestations, there is a lack of literature addressing atypical presentations and their unique features, including the absence of acute pain and the development of complications such as thrombotic events and acute chest syndrome [ 9 , 10 ]. Understanding the heterogeneous nature of sickle cell disease is crucial, as it presents a wide range of clinical manifestations [ 11 , 12 ]. Diagnostic challenges are encountered in identifying atypical sickle cell crises, as evidenced by the delayed diagnosis in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…50 A study by David and colleagues reported that patients on chronic, high-dose opioid therapy with inadequate response had successful transition to sublingual buprenorphine. 51 The conversion strategy was done through a multidisciplinary team and performed under careful monitoring for the risk of withdrawal symptoms; the converted patients experienced minimal adverse effects. 51 According to the researchers, only a few patients reverted back to using strong opioids.…”
Section: Acute and Chronic Pain In Scdmentioning
confidence: 99%
“…51 The conversion strategy was done through a multidisciplinary team and performed under careful monitoring for the risk of withdrawal symptoms; the converted patients experienced minimal adverse effects. 51 According to the researchers, only a few patients reverted back to using strong opioids. 51…”
Section: Acute and Chronic Pain In Scdmentioning
confidence: 99%
“…[149][150][151] Dose reductions in such patients are often well-tolerated, sometimes even improving pain severity; in some patients transition to partial agonist therapy with buprenorphine can both reduce risks and improve symptom control. 152,153…”
Section: Th E Psychi Atry Of Opioids I N Sick L E Ce L L Dise Asementioning
confidence: 99%
“…The risks of opioid therapy, principally incurred by patients on prolonged therapy at high doses, can then be compared to benefits 149–151 . Dose reductions in such patients are often well‐tolerated, sometimes even improving pain severity; in some patients transition to partial agonist therapy with buprenorphine can both reduce risks and improve symptom control 152,153 …”
Section: The Psychiatry Of Opioids In Sickle Cell Diseasementioning
confidence: 99%